Understanding terrorism: contested concept, conflicting perspectives and shattering consequences - Moten, Abdul Rashid (IIUM Press, 2010)
Terrorism is an old phenomenon but its modern manifestation was first noted in the 19th century with the anarchist group who assassinated Czar Alexander II in 1881. Since then it has continued unabated but its intensity and frequency increased in the 21st century. This study examines the trends in international terrorism and, in particular, analyses its causes and consequences. Based upon extensive literature and documentary research, this study found at least three perspectives that explain terrorism either as a reaction to socioeconomic deprivation or as the product of religious fundamentalism or as a legitimate struggle to wipe out injustices perpetrated by the powerful against the powerless. Muslims condemn terrorism and suggest that the Western powers cease their policies of victimising the vulnerable populations, of sponsoring terrorists, of siding with Israel, and of denying others their right to liberty and sovereignty.